Somatic mutations in clonally expanded cytotoxic T lymphocytes in patients with newly diagnosed rheumatoid arthritis - P. Savola (Nature Portfolio, 2017)
Accumulation of somatic mutations in lymphocytes is a feature of some cancers. Here the authors show that patients with recent onset of rheumatoid arthritis also accumulate mutations in their expanded CD8+ effector memory T cell pool independent of cancer association.